Current status of coronary risk factors among rural Malays in Malaysia - Khan, Rahmattullah; Nawawi, Hapizah; Nor, Idris; Noor, Ismail; Karim, Norimah; Arshad, Fatimah; Yusoff, Khalid (Lippincott Williams & Wilkins, 2002)
Background Coronary heart disease (CHD) is the leading cause of death in Malaysia, despite its status as a developing country. The rural population is thought to be at low risk. Objective To investigate the prevalence of risk factors and global risk profile among rural Malays in Malaysia. Methods We studied 609 rural Malay subjects (346 females, 263 males; age range 30–65 years). Blood pressure (BP), body mass index (BMI), waist–hip ratio (WHR), smoking habits and family history of premature CHD were documented. Fasting blood samples were analysed for serum lipids, lipoprotein (a), plasma glucose and fibrinogen. Oral glucose tolerance tests were performed using 75 g anhydrous glucose. Results The prevalence of hypercholesterolemia for total cholesterol concentrations of ≥ 5.2, ≥6.5 and ≥7.8 mmol/l were 67.3, 30.5 and 11.8% respectively. There was a high prevalence of low serum high-density lipoprotein cholesterol (13.1%), hypertension (30.3%), smokers (24.4%), diabetes (6.4%), impaired fasting glucose or glucose tolerance (13.9%), overweight or obesity (44.7%) and increased WHR (48.5%). Global risk assessment showed that 67.3% of the study population were at risk, with 15.9, 18.9 and 32.5% in the mild, moderate and high risk categories respectively. Conclusion Prevalence of risk factors was high in the rural population. Global risk assessment showed a high-risk profile with two-thirds being at risk, and one-third being categorized into the high-risk group. Although rural communities were considered at low risk of developing CHD, this is changing fast, possibly due to the rapid socio-economic development, in addition to underlying genetic predisposition.